2007
DOI: 10.1038/oby.2007.638
|View full text |Cite
|
Sign up to set email alerts
|

Short‐Term Effects of a “Health‐At‐Every‐Size” Approach on Eating Behaviors and Appetite Ratings

Abstract: PROVENCHER, VÉ RONIQUE, CATHERINE BÉ GIN, ANGELO TREMBLAY, LYNE MONGEAU, SONIA BOIVIN, AND SIMONE LEMIEUX. Short-term effects of a "Health-At-Every-Size" approach on eating behaviors and appetite ratings. Obesity. 2007;15:957-966. Objective: To assess the effects of a "Health-At-EverySize" (HAES) intervention on eating behaviors and appetite ratings in 144 premenopausal overweight women. Research Methods and Procedures: Women were randomly assigned to one of the 3 groups: HAES group, social support (SS) group,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
0
5

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(78 citation statements)
references
References 47 publications
2
71
0
5
Order By: Relevance
“…Moreover, we thought that changes in eating behaviors which were found to be significant in response to our intervention 25 could be translated into concrete and significant changes in food consumption and nutrient intakes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we thought that changes in eating behaviors which were found to be significant in response to our intervention 25 could be translated into concrete and significant changes in food consumption and nutrient intakes.…”
Section: Discussionmentioning
confidence: 99%
“…Inclusion and exclusion criteria have been previously reported (Provencher et al, 2007). Women who participated in the present study were recruited between September 2003 and January 2005, as previously described (Provencher et al, 2007). Women were tested during the follicular phase of their menstrual cycle to control for potential impact of hormonal variation on dietary variables.…”
Section: Participantsmentioning
confidence: 99%
“…More specific subscales can also be derived from these three general eating behaviors (Westenhoefer, Stunkard, & Pudel, 1999;Bond, McDowell, & Wilkinson, 2001): rigid restraint, flexible restraint, habitual susceptibility to disinhibition, emotional susceptibility to disinhibition, situational susceptibility to disinhibition, internal hunger, and external hunger, as previously described (Provencher et al, 2007). The Binge Eating Scale is a 16-item validated questionnaire (Gormally, Black, Daston, & Rardin, 1982) which assesses binge eating severity.…”
Section: Eating Behaviorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inclusion of intensive stress management training in a non-dieting group programme for overweight women has been shown to enhance stress management and medical symptom outcomes, but not weight outcomes (20) . To date, among studies of group non-dieting interventions (5,7,10,(16)(17)(18)(19)21) , only one has reported attendance/ completion data (12) . Rapoport et al (12) reported significantly higher binge eating, but no significant BMI, depression or demographic differences in women who attended fewer than seven out of ten sessions compared with those who attended at least seven sessions.…”
mentioning
confidence: 99%